The historical representation of the Madeira Mamoré Railroad and the reception of the work A Ferrovia do Diabo in the Rio and São Paulo press in the 1960s and 1970s: A representação histórica da Estrada de Ferro Madeira Mamoré e a recepção da obra A Ferrovia do Diabo na imprensa carioca e paulista nos anos de 1960 e 1970 (Revista de História da UEG (REVHIST), 2022)
This article analyzes the impact that the work A Ferrovia do Diabo, by Manoel Rodrigues Ferreira, had on the construction of a new historical representation of the Madeira Mamoré Railroad - in the 1960s and 1970s, through the analysis of criticism in articles from Rio de Janeiro and São Paulo newspapers that hosted Rodrigues Ferreira's book. The theoretical foundation took into account studies on the reception of printed texts in our contemporary times, studies on journalistic criticism in the 20th century, as well as the use of Roger Chartier's concept of representation. The research results indicated that the work A Ferrovia do Diabo, from the 1970s onwards, reprinted in the imagination of journalistic critics the representation of Madeira Mamoré as a tragic, dark and melancholic railway.Keywords: Historical representations. Madeira Mamoré. Critical reception. Ferrovia do Diabo. Press.